2023
DOI: 10.1109/tnnls.2021.3106777
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Integration Between Machine Learning and Agent-Based Modeling: A Multidisciplinary Review

Abstract: Agent-based modeling (ABM) involves developing models in which agents make adaptive decisions in a changing environment. Machine-learning (ML) based inference models can improve sequential decision-making by learning agents' behavioral patterns. With the aid of ML, this emerging area can extend traditional agent-based schemes that hardcode agents' behavioral rules into an adaptive model. Even though there are plenty of studies that apply ML in ABMs, the generalized applicable scenarios, frameworks, and procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 154 publications
0
12
0
Order By: Relevance
“…5 There are already a handful of literature reviews on using ML in ABMS. Zhang et al (2021) review literature on ML for the agents' decision-making, distinguishing between micro-agent-level situational awareness learning, micro-agent-level behaviour intervention, macro-ABMS-level emulator, and sequential decision-making. Dahlke et al (2020) provide a general literature review on using ML for the structural specifications and outputs of ABMS.…”
Section: 3mentioning
confidence: 99%
“…5 There are already a handful of literature reviews on using ML in ABMS. Zhang et al (2021) review literature on ML for the agents' decision-making, distinguishing between micro-agent-level situational awareness learning, micro-agent-level behaviour intervention, macro-ABMS-level emulator, and sequential decision-making. Dahlke et al (2020) provide a general literature review on using ML for the structural specifications and outputs of ABMS.…”
Section: 3mentioning
confidence: 99%
“…Several prior reviews have described how ML can be leveraged in computational modeling, e.g., by Alber et al (2019) and by Peng et al (2021). In addition, the idea of synergistically integrating ML and ABM (Figure 2) has existed since at least Rand's (2006) early report, and includes more recent works such as by Giabbanelli (2019), Brearcliffe and Crooks (2021), and Zhang et al (2021). The remainder of our present Review focuses more on the utility of ML within ABMs, and attempts to offer some guiding principles on how and when these integrations are feasible in simulating different scales of biology.…”
Section: • Parameter Calibration and Surrogate Models Of Abmsmentioning
confidence: 99%
“…As an example of how to interpret this diagram, note that mode ②, "behavior intervention", entails application of "online" ML methods to modify agent behavior/action policies, which is essentially reinforcement learning. Note that this illustration is adapted from one that appears in Zhang et al (2021), where further details may be found.…”
Section: Figurementioning
confidence: 99%
“…For example, ML provides methods to extend agent based modelling and participatory modelling into adaptive models where agents' behaviours are hardcoded. This allows fishery managers and stakeholders to explore model scenarios, such as behaviour intervention, sequential decision-making, and situational awareness learning (Zhang et al, 2021). Researchers have explored the use of reinforcement learning based methods to address IUU fishing.…”
Section: Procedural Trustmentioning
confidence: 99%